Irrupción y ficcionalización de lo real: El uso de fotografías en Marías, Brizuela y Vásquez - Gustafsson, Jan (Diálogos Latinoamericanos, 2018)
The object of this article is the use of photographs in contemporary Hispanic narrative fiction. More specifically, I analyze the use of photographs in three recent novels, Así empieza lo malo, by Javier Marías, Una misma noche, by Leopoldo Brizuelas, and, La forma de las ruinas, by Juan Gabriel Vásquez. In the introduction, I suggest some elements of theory and give a very brief state of the art regarding the use of photography in contemporary fiction in Spanish as well as of the academic discussion of the subject. My results show important similarities, but also differences in the use of photography in these works of fiction. A main effect of the use of a photographic image in a narrative text is metafictional: “reality” bursts into the fiction, but is also absorbed by it. Furthermore, the photographs serve to stress the importance of the central themes of these novels: evil and violence.